Feasibility study of novel DME fuel injection Equipment: Part 1- fuel injection strategies and spray characteristics. (1st September 2022) - Mukherjee, Nalini Kanta; Valera, Hardikk; Unnithan, Sarat; Kumar, Vikram; Dhyani, Vipin; Mehra, Shanti; Tripathi, Ayush; Nene, Devendra; Agarwal, Avinash Kumar
Graphical abstract: Highlights: 3-D CFD model for off-highway tractor engine was developed. 3-D CFD model was calibrated using the experimental data. Customized fuel injection equipment for DME was explored. DME exhibited faster evaporation than baseline diesel. Novel FIE showed superior MEIP and spray characteristics. Abstract: The Methanol Economy is projected as a sustainable solution to the impending global energy crisis. Methanol and Dimethyl Ether (DME) are projected as exceptional alternative fuel solutions to power future mobility, ensuring the continued growth of internal combustion engines (ICEs) in an environmentally sustainable manner. In this study, the technical feasibility of DME as an alternative to diesel is assessed using a three-dimensional computational fluid dynamics (3D-CFD) simulation approach. A novel fuel injection equipment (FIE) is computationally assessed for DME induction into the engine. A water-cooled, naturally-aspirated, compression ignition (CI) engine used for off-highway application is simulated for using DME as a complete replacement of mineral diesel. First, the baseline diesel combustion calibration is done to validate the simulation model using experimental data. For this, a 3D CFD closed-cycle model of a detailed chemistry-based solver is used. Spray characteristics revealed that DME exhibited faster evaporation than diesel, resulting in lesser fuel-rich pockets in the combustion chamber. DME fueled engine is anticipated to be more thermally efficient due to DME combustion's lower turbulence kinetic energy, which reduces gas side heat transfer through the cylinder walls. DME's higher total in-cylinder mass results in a lower swirl momentum and a reduced swirl ratio for the DME. The proposed FIE promotes a superior Mean Effective Injection Pressure (MEIP) and ameliorated spray penetration characteristics. This study provides systematic guidelines for selecting an appropriate FIE for DME, with Nozzle Through Flow (NTF) and MEIP tuned to achieve the best possible spray characteristics to develop an efficient and clean combustion system for the given application.